Analisa Bibliometrik Kejadian Maloklusi yang Berhubungan dengan Stunting - Istikharoh, Feni; madani, insi (E-Prodenta Journal of Dentistry, 2026)
Introduction: Indonesia currently still has a high incidence of dental and oral health problems. Based on the 2018 National Basic Health Research (Riskesdas), it was stated that as many as 57.6% of Indonesians have dental and oral problems. Dental and oral problems that are often found include malocclusion. Malocclusion has two basic causes, namely intrinsic factors and extrinsic factors. One example of an intrinsic factor is nutritional status. Nutritional status generally affects the growth and development of the body and especially the growth and development of teeth and mouth. Stunting (poor nutritional status) can cause tooth malformation, high prevalence of caries, easy injury to soft tissue, malocclusion of teeth, inhibited development of facial and jaw bones, and the presence of crowded teeth. Objective: To analyze the development of malocclusion events related to stunting. Method: This study uses a bibliometric analysis method using R software, from 159 journals obtained from the Scopus database in the period 2004-2024. Results: This study found that stunting (short nutritional status) can cause malocclusion in children of growth age. It was also found that the most common malocclusion in children is crowded teeth. Conclusion: From the bibliometric analysis conducted, in-depth insights were found regarding topic trends in research on malocclusion events related to stunting, an increase in the number of publications and research trends from year to year continue to develop, with various new topics and approaches emerging.